2008
DOI: 10.1080/00103620801925661
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ceramic and Polytetrafluoroethene/Quartz Suction Cups for Sampling Inorganic Ions in Soil Solution

Abstract: Because the widely used ceramic cups are reported to release, adsorb, and filter dissolved nutrients from soil solution samples, inert cups made of poly(tetrafluoroethene) (PTFE) are frequently proposed as a more reliable alternative. A ceramic and a PTFE/quartz cup were compared with each other in this laboratory study. The PTFE/ quartz cup was the most suited for pH measurements. Because only the ceramic cup samples both ammonium and nitrate in a satisfactory way, this cup type is recommended for nitrogen (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Aqueous solutions of N sources such as (NH 4 ) 2 SO 4 , NH 4 Cl and KNO 3 were respectively sprayed on the ground within four individual plots in four equal monthly doses (JulyOctober) in 2006 and in five equal monthly doses (June-October) in 2007 at a rate of 4.5 g per m 2 each year, corresponding with 5.0 mm rainfall each; tap water was added only to the control. According to the depth of A-horizons and the distribution of tree roots in underlying soil, two sets of porous ceramic suction cups (3.1 cm in diameter and 7 cm in height) were installed at 15 cm and 60 cm depths, respectively, to collect soil solutions of organic layers and beyond root zones (Vandenbruwane et al, 2008). To eliminate the disturbance of soil, soil auger with a diameter of 3.3 cm was used to establish the holes down to 15 cm and 60 cm depths, respectively, and the suction cups connected to PVC tubes were fixed closely inside the holes.…”
Section: Effects Of N Addition On Soil Solution Chemistry Under Foresmentioning
confidence: 99%
“…Aqueous solutions of N sources such as (NH 4 ) 2 SO 4 , NH 4 Cl and KNO 3 were respectively sprayed on the ground within four individual plots in four equal monthly doses (JulyOctober) in 2006 and in five equal monthly doses (June-October) in 2007 at a rate of 4.5 g per m 2 each year, corresponding with 5.0 mm rainfall each; tap water was added only to the control. According to the depth of A-horizons and the distribution of tree roots in underlying soil, two sets of porous ceramic suction cups (3.1 cm in diameter and 7 cm in height) were installed at 15 cm and 60 cm depths, respectively, to collect soil solutions of organic layers and beyond root zones (Vandenbruwane et al, 2008). To eliminate the disturbance of soil, soil auger with a diameter of 3.3 cm was used to establish the holes down to 15 cm and 60 cm depths, respectively, and the suction cups connected to PVC tubes were fixed closely inside the holes.…”
Section: Effects Of N Addition On Soil Solution Chemistry Under Foresmentioning
confidence: 99%
“…These include vacuum lysimeters (also referred to as porous cups/tubes or suction cups), suction plate or tension plate lysimeters, pan or zero-tension lysimeters, wick samplers, and resin boxes (Weihermüller et al, 2007). Lysimeters of varied types provide a method for frequent measurement of soil pore water and may be placed at multiple depths to monitor solute movement; however, selection of a suitable sampler material depending on the solutes of interest is imperative (Weihermüller et al, 2007;Vandenbruwane et al, 2008). In agricultural systems, it is likely that lysimeters will have to be removed and reinstalled to accommodate certain machinery.…”
Section: Carbon Dioxide Removalmentioning
confidence: 99%
“…Beier and Hansen (1992), who compared ceramic and polytetrafluoroethene cup lysimeters for soil water sampling of Na, K, Ca, Al, NH 4 , H, and non‐purgeable organic C reported that neither sampler contaminated the soil water samples nor retained any substances. Vandenbruwane et al (2008), however, observed that ceramic lysimeters adequately sampled most cations except Al. Levin and Jackson (1977), who compared hollow microfiber and porous ceramic cup lysimeters for sampling soil water containing Ca, Mg, and orthophosphate (PO 4 –P) found that neither extractor altered the chemical composition of the leachate.…”
mentioning
confidence: 90%